Dual-source computed tomography of the lung with spectral shaping and advanced iterative reconstruction: potential for maximum radiation dose reduction - Wetzl, Matthias; May, Matthias; Weinmann, Daniel; Hammon, Matthias; Treutlein, Christoph; Zeilinger, Martin; Kiefer, Alexander; Trollmann, Regina; Wölfle, Joachim; Uder, Michael; Rompel, Oliver (Pediatric Radiology, 2020)
Background: Radiation dose at CT should be as low as possible without compromising diagnostic quality. Objective: To assess the potential for maximum dose reduction of pediatric lung dual-source CT with spectral shaping and advanced iterative reconstruction (ADMIRE). Materials and methods: We retrospectively analyzed dual-source CT acquisitions in a full-dose group (FD: 100 kV, 64 reference mAs) and in three groups with spectral shaping and differing reference mAs values (Sn: 100 kV, 96/64/32 reference mAs), each group consisting of 16 patients (age mean 11.5 years, standard deviation 4.8 years, median 12.8 years, range 1.3–18 years). Advanced iterative reconstruction of images was performed with different strengths (FD: ADMIRE Level 2; Sn: ADMIRE Levels 2, 3 and 4). We analyzed dose parameters and measured noise. Diagnostic confidence and detectability of lung lesions as well as anatomical structures were assessed using a Likert scale (from 1 [unacceptable] to 4 [fully acceptable]). Results: Compared to full dose, effective dose was reduced to 16.7% in the Sn 96 group, 11.1% in Sn64, and 5.5% in Sn32 (P<0.001). Noise values of Sn64ADM4 did not statistically differ from those in FDADM2 (45.7 vs. 38.9 Hounsfield units [HU]; P=0.132), whereas noise was significantly higher in Sn32ADM4 compared to Sn64ADM4 (61.5 HU; P<0.001). A Likert score >3 was reached in Sn64ADM4 regarding diagnostic confidence (3.2) and detectability of lung lesions (3.3). For detectability of most anatomical structures, no significant differences were found between FDAM2 and Sn64ADM4 (P≥0.05). Conclusion: In pediatric lung dual-source CT, spectral shaping together with ADMIRE 4 enable radiation dose reduction to about 10% of a full-dose protocol while maintaining an acceptable diagnostic quality.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Adolescents; Advanced iterative reconstruction; Children; Dual-source computed tomography; Lung; Radiation dose reduction; Spectral shaping; Tin prefiltration